Enhancing psychological interventions for post-traumatic stress disorder (PTSD) treatment with memory influencing drugs - Marchetta, Enrico; Mancini, Giulia F.; Morena, Maria; Campolongo, Patrizia (Current Neuropharmacology, 2023)
Post-traumatic stress disorder (PTSD) is a chronic psychiatric disease resulting from the experience or witnessing of traumatic events. Persistent PTSD symptoms impair patients' daily quality of life, jeopardizing sleep, mood, sociability, and arousal. Recommended psychological or pharmacological interventions are effective only in a small portion of patients and often lead to relapse. Thus, there is a critical need to address a lack of advancement in the treatment of PTSD. The combination of psychological interventions, aimed at facilitating the extinction of the traumatic memory, and pharmacological medications, represents a promising tool for PTSD treatment. Timely use of psychotherapy in conjunction with pharmacological treatments, rather than monotherapy, could thus determine a synergistic effect by potentiating the effects of psychological interventions. In such a scenario, drugs that modulate cognitive processes involved in the development and/or persistence of post-traumatic symptomatology could be of great help to improve the outcome of psychotherapies and patients' prognosis. The purpose of the present article is to review the current data available from clinical trials on combined pharmacological treatments with psychological interventions in PTSD therapy. An overview of findings from animal studies that prompted clinical research is also discussed. (PsycInfo Database Record (c) 2023 APA, all rights reserved)
Keywords: Drug Therapy; Extinction; Extinction (Learning); Intervention; MDMA; Memory; Posttraumatic Stress Disorder; Psychotherapy; Symptoms; cannabis; cognitive enhancers; fear; psychotherapy; trauma